2000
DOI: 10.1302/0301-620x.82b2.0820276
|View full text |Cite
|
Sign up to set email alerts
|

Influence of extracorporeal irradiation on the reintegration of autologous grafts of bone and joint

Abstract: We studied the effects of irradiation on the reintegration of autologous osteoarticular grafts over a period of 24 weeks in a canine model. In 16 foxhounds the medial femoral condyle was resected, irradiated and immediately replanted. In the control group resection and replantation were performed without irradiation. Reintegration was assessed by macroscopic analysis, histology, radiography and gait analysis.Reintegration was equal at 12 weeks, but significantly inferior in the irradiated group after 24 weeks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
22
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 44 publications
(52 reference statements)
2
22
0
Order By: Relevance
“…For complete eradication, bone tumours require an irradiation dose of at least 80 Gy with a higher dose required under anoxic conditions. Doses above 27,000 Gy affect the biomechanical properties of a bone graft [22]. The frequency of delayed unions for irradiated autografts at 12 weeks in rats has been related to the irradiation dose: 16% at 1 kGy, 24% at 5 kGy, and 100% at 25 kGy [23].…”
Section: Discussionmentioning
confidence: 99%
“…For complete eradication, bone tumours require an irradiation dose of at least 80 Gy with a higher dose required under anoxic conditions. Doses above 27,000 Gy affect the biomechanical properties of a bone graft [22]. The frequency of delayed unions for irradiated autografts at 12 weeks in rats has been related to the irradiation dose: 16% at 1 kGy, 24% at 5 kGy, and 100% at 25 kGy [23].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also conformed this point of view and believe this dose should be sufficient to produce a tumor elimination rate of 100% (23,26). Studies by Sabo et al (27) and Currey et al (28) have demonstrated a radiation dose-dependent reduction in strength and also suggested reduced revascularization and osteoconductive properties, thereby increasing the time to union and incorporation. Therefore, the present study used a radiation dose of 50 Gy.…”
Section: Discussionmentioning
confidence: 78%
“…Higher doses have been shown to reduce the revascularization and osteoconductive capability of the graft, thereby increasing the time to union and incorporation [30-32]…”
Section: Discussionmentioning
confidence: 99%